Children's Lifeworlds in a Global City: Singapore - Soo, Li Mei Johannah; Karthikeyan, Nanthini; Lim, Kam Ming.; Bartholomaeus, Clare; Yelland, Nicola (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book examines connections between policy contexts, school experiences and everyday activities of children growing up in the global city of Singapore. In particular, it explores how Singapore children's everyday experiences inside and outside of school shape their orientations towards educational success. Alongside an analysis of school life and educational policies, it also considers children's out-of-school activities, including leisure, homework, and enrichment activities, and connections between these and their school-based activities. The book draws on empirical data from Primary 4 classes in two Singapore schools in the form of student-completed surveys, classroom ethnographies, student responses to a learning dialogues activity, and a re-enactment of one child's out-of-school life, as well as curriculum and policy analysis. It provides readers with an in-depth understanding of Singapore Primary 4 children's experiences inside and outside of school, including the structure of timetables and pedagogical approaches encountered in school lessons, children's enjoyment of activities inside and outside of school, children's engagement and wellbeing at school, and the impact of Singapore's educational policies on children's learning experiences. Moving beyond a simplistic focus on Singapore children's academic performance in international high-stakes testing, the book offers a comprehensive exploration of their lives inside and outside of school. This holistic approach is unique in the Singapore context and contributes to a greater understanding of children's everyday lives in the city.
Chapter 1. Introduction -- Chapter 2. Timetabling and routines -- Chapter 3. Pedagogical encounters -- Chapter 4. School engagement and orientations to success -- Chapter 5. School belonging and wellbeing -- Chapter 6. Activities outside of school -- Chapter 7. Synthesis.
Keywords: Early childhood education; Education; Children; Education and state; Educational sociology; Sociology; Social groups; Early Childhood Education; Childhood Education; Educational Policy and Politics; Sociology of Education; Sociology of Family, Youth and Aging